Right to Education: An Assessment: Examining the Implementation and Impact of the Right to Education Act in India (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The Right to Education (RTE) is an act of Parliament of India enacted on 4 August 2009, which describes the modalities of the importance of free and compulsory education for children between ages 6-14 year in India under Article 21 A of the Indian constitution. India becomes one of 135 countries to make education a fundamental right of every child when act came into force on April 1, 2010. The right of children to free and compulsory education means that every child has a right to full time elementary education of satisfactory and equitable quality in a formal school which satisfices certain essential norms and standards.